Demographic analysis on academic staff's job satisfaction in Malaysian Research Universities. - Sadeghi, Amir; Lope Pihie, Zaidatol Akmaliah; Elias, Habibah; Foo, Say Fooi (Universiti Putra Malaysia Press, 2012)
Academic staff's performance plays a vital role in higher education institutions to enjoy high quality research and excellent teaching. It can be stated that academic staff's job satisfaction has influence on their quality of performance. Hence, the factors which may affect their level of job satisfaction is critical to higher education institutions. This research is an attempt to examine the differences in the job satisfaction among academic staff in terms of their demographic characteristics. The total population was 3430 academic staff working at three Malaysian Research Universities, whereby out of this number, 400 were surveyed, making up a response rate of 74.5%. Using Wood Faculty Job Satisfaction/ Dissatisfaction Scale, results are revealed in terms of intrinsic, extrinsic, and overall job satisfactions, whereby the academic staffs were found to be at the moderate satisfaction level. Gender, academic rank, and age were identified as the influencing factors for academic staff job satisfaction, while their level of education was not.